Using transcription of six Puccinia triticina races to identify the effective secretome during infection of wheat - Bruce, Myron; Neugebauer, Kerri A.; Joly, David L.; Migeon, Pierre; Cuomo, Christina A.; Wang, Shichen; Akhunov, Eduard; Bakkeren, Guus; Kolmer, James A.; Fellers, John P. (Frontiers in Plant Science, 2014)
Wheat leaf rust, caused by the basidiomycete Puccinia triticina, can cause yield losses of up to 20% in wheat producing regions. During infection, the fungus forms haustoria that secrete proteins into the plant cell and effect changes in plant transcription, metabolism and defense. It is hypothesized that new races emerge as a result of overcoming plant resistance via changes in the secreted effector proteins. To understand gene expression during infection and find genetic differences associated with races, RNA from wheat leaves infected with six different rust races, at six days post inoculation, was sequenced using Illumina. As P. triticina is an obligate biotroph, RNA from both the host and fungi were present and separated by alignment to the P. triticina genome and a wheat EST reference. A total of 222,571 rust contigs were assembled from 165 million reads. An examination of the resulting contigs revealed 532 predicted secreted proteins among the transcripts. Of these, 456 were found in all races. Fifteen genes were found with amino acid changes, corresponding to putative avirulence effectors potentially recognized by 11 different leaf rust resistance (Lr) genes. Thirteen of the potential avirulence effectors have no homology to known genes. One gene had significant similarity to cerato-platanin, a known fungal elicitor, and another showed similarity to fungal tyrosinase, an enzyme involved in melanin synthesis. Temporal expression profiles were developed for these genes by qRT-PCR and show that the 15 genes share similar expression patterns from infection initiation to just prior to spore eruption.